Rice Yields at Different Dosages of Kieserite and Planting Systems - Rozen, Nalwida; Kasim, Musliar; Dwipa, Indra (Department of Agronomy and Horticulture, IPB University, 2023)
Rice stands as an important staple crop in Indonesia and Asia, prompting endeavors to enhance its production. One such technology, aimed at intensifying rice cultivation, involves optimizing plant density utilizing the